2014
DOI: 10.1002/dvdy.24140
|View full text |Cite
|
Sign up to set email alerts
|

The drosophila Chmp1 protein determines wing cell fate through regulation of epidermal growth factor receptor signaling

Abstract: BACKGROUND: Receptor down-regulation by the multivesicular body (MVB) pathway is critical for many cellular signaling events. MVB generation is mediated by the highly conserved ESCRT (0, I, II, and III) protein complexes. Chmp1 is an ESCRT-III component and a putative tumor suppressor in humans. However, published data on Chmp1 activity are conflicting and its role during tissue development is not well defined. RESULTS: We investigated the function of Drosophila Chmp1 and found that it is an essential gene. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 57 publications
2
17
0
Order By: Relevance
“…Ubiquitous silencing of Chmp1 or Usp8 in Drosophila is lethal before the pupal stage, so we used transgenic fly lines expressing silencing hairpins under the control of the UAS promoter [ 69 ] together with the specific wing Gal4 driver MS1096-Gal4 inducing the expression of the UAS constructs in the dorsal wing layer. Consistent with previous studies showing the role of these two genes in wing development [ 63 , 68 , 70 ], silencing either Chmp1 or Usp8 resulted in a similar curved and growth defective wing phenotype ( Fig 6B ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Ubiquitous silencing of Chmp1 or Usp8 in Drosophila is lethal before the pupal stage, so we used transgenic fly lines expressing silencing hairpins under the control of the UAS promoter [ 69 ] together with the specific wing Gal4 driver MS1096-Gal4 inducing the expression of the UAS constructs in the dorsal wing layer. Consistent with previous studies showing the role of these two genes in wing development [ 63 , 68 , 70 ], silencing either Chmp1 or Usp8 resulted in a similar curved and growth defective wing phenotype ( Fig 6B ).…”
Section: Resultssupporting
confidence: 92%
“…Using an EGFP reporter gene expressed under Notch Responsive Elements (NRE) and the driver engrailed -Gal4 (en-Gal4) to induce the silencing construct in the posterior part of the wing imaginal disc, we observed that silencing endogenous Chmp1 resulted in an enlarged domain of EGFP expression both in the domain of engrailed ( en ) expression and slightly beyond ( Fig 6C ). Defects outside the domain of shCHMP1 expression is in accordance with a non-cell autonomous role of ESCRT proteins in the regulation of developmental signals [ 70 , 73 80 ]. This resulted in observable wing margin defects at the adult stage ( Fig 6C ).…”
Section: Resultsmentioning
confidence: 99%
“…To circumvent any potential detrimental effects at the tissue or organism levels, the FLPout method [27] was used to express transgenes in a few fat body cells surrounded by wild-type cells (see Methods and Additional file 1: Figure S1). The transgenes used were: a dominant negative form of Shibire – the Drosophila homologue of the Dynamin GTPase that is required for the scission of the newly formed endosomes from the plasma membrane – (ShiK44A) which blocks the budding of endocytic vesicles from the plasma membrane [28], a dsRNA targeting Rab5 [14] that efficiently inhibits the early endosomal Rab5 protein (Additional file 2: Figure S2), a dominant negative mutant of Rab4 (Rab4SN) which blocks the endosomal recycling pathway [15] and a dsRNA against Chmp1 – a component of the ESCRT machinery – which impairs the formation of intraluminal vesicles in the MVB [2931]. Lastly, a dominant negative mutant of Rab7 (Rab7TN) was added as a control because Rab7 is essential for lysosomes biogenesis and maintenance of the perinuclear lysosome compartment [17, 32, 33].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, they may function in recruiting and activating the VPS4-Vta1 complex, and promoting disassembly of ESCRT-III, but perhaps in a non-essential manner (Lottridge et al, 2006;Yang et al, 2012). In Drosophila, CHMP1 was found to be essential for the regulation of epidermal growth factor receptor (EGFR) signaling (Valentine et al, 2014). Only a single VPS60 (CHMP5) is found in yeast, and single highly conserved orthologs were identified in insects and humans (Table 1, Fig.…”
Section: Escrt-iiimentioning
confidence: 99%